Bioimpedance index for measurement of total body water in severely malnourished children: Assessing the effect of nutritional oedema. Issue 3 (June 2016) - Girma, Tsinuel; Kæstel, Pernille; Workeneh, Netsanet; Mølgaard, Christian; Eaton, Simon; Andersen, Gregers S.; Michaelsen, Kim F.; Friis, Henrik; Wells, Jonathan C.K.
Summary: Background & objectives: Restoration of body composition indicates successful management of severe acute malnutrition (SAM). Bioimpedance (BI) index (height 2 /resistance) is used to predict total body water (TBW) but its performance in SAM, especially with oedema, requires further investigation. Subjects/Methods: Children with SAM (mid-arm circumference <11.0 cm or weight-for-height <70% of median of NCHS reference and/or nutritional oedema) admitted to Jimma University Hospital were included. Tetrapolar-whole-body impedance (Z), resistance (R) and reactance (Xc) were measured at 50 and 200 kHzs. Pre- and post-deuterium dose saliva samples were analysed using isotope-ratio mass spectrometry. TBW was regressed on H 2 /Z. Xc and R were height (H)-indexed, and Xc/H plotted against R/H. Results: Thirty five children (16 non-oedematous and 19 oedematous) with median (interquartile range) age of 42 (26–54) months were studied. Height-for-age z-score (mean ± SD) was low in both non-oedematous (−3.9 ± 2.8) and oedematous (−3.6 ± 1.7) children. Oedematous children had lower BI parameters than non-oedematous (p < 0.001) and hence higher H 2 /Z for a given amount of TBW. At both 50 and 200 kHz, association between H 2 /Z and TBW was stronger in non-oedematous children than oedematous (60% higher coefficient of determination and 20% lower standard error of estimate). Intercepts and regression estimates at 50 and 200 kHz were similar, in both oedematous and non-oedematous children. Conclusions: In children with oedematous SAM, BI index was weak in predicting TBW. Moreover, predicted TBWs at 200 kHz and 50 kHz did not differ and hence BI measurement at 50 kHz is still practical for TBW estimation.